(5c-3)(7c+6)=

Simple and best practice solution for (5c-3)(7c+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5c-3)(7c+6)= equation:


Simplifying
(5c + -3)(7c + 6) = 0

Reorder the terms:
(-3 + 5c)(7c + 6) = 0

Reorder the terms:
(-3 + 5c)(6 + 7c) = 0

Multiply (-3 + 5c) * (6 + 7c)
(-3(6 + 7c) + 5c * (6 + 7c)) = 0
((6 * -3 + 7c * -3) + 5c * (6 + 7c)) = 0
((-18 + -21c) + 5c * (6 + 7c)) = 0
(-18 + -21c + (6 * 5c + 7c * 5c)) = 0
(-18 + -21c + (30c + 35c2)) = 0

Combine like terms: -21c + 30c = 9c
(-18 + 9c + 35c2) = 0

Solving
-18 + 9c + 35c2 = 0

Solving for variable 'c'.

Factor a trinomial.
(-6 + -7c)(3 + -5c) = 0

Subproblem 1

Set the factor '(-6 + -7c)' equal to zero and attempt to solve: Simplifying -6 + -7c = 0 Solving -6 + -7c = 0 Move all terms containing c to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -7c = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -7c = 0 + 6 -7c = 0 + 6 Combine like terms: 0 + 6 = 6 -7c = 6 Divide each side by '-7'. c = -0.8571428571 Simplifying c = -0.8571428571

Subproblem 2

Set the factor '(3 + -5c)' equal to zero and attempt to solve: Simplifying 3 + -5c = 0 Solving 3 + -5c = 0 Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5c = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5c = 0 + -3 -5c = 0 + -3 Combine like terms: 0 + -3 = -3 -5c = -3 Divide each side by '-5'. c = 0.6 Simplifying c = 0.6

Solution

c = {-0.8571428571, 0.6}

See similar equations:

| 4(x-2)-7x=1 | | Y(y-1)(y+2)=0 | | 33/20 | | 2x+0.5x+0.25x=12 | | 7.15=5.5u | | 4x/8y= | | 4.9=0.6 | | 700(1000)+1200x=1000000 | | 32=8s | | 0=(4x-1)(x-1) | | a=3.14(63)(63) | | 3x+2y=152 | | c=2(3.14)(126) | | 55x-14-35x=-133 | | 90x-1400-x^2=0 | | (X^6)^6/x^3 | | 48x-13-24x=-358 | | y=(x^2-8x+12)(x+1) | | (4/3)(3.14) | | -12(x+6)=4(x+6) | | a=3.14(13)(13) | | x+(x*2.24)=2200 | | c=2(3.14)(26) | | -13-3(t-5)= | | Logx=(x^2-12) | | X*2-6x-23=0 | | 15x+53=83 | | 37x-14+19x=-105 | | .04x+.07(11000-x)=660.00 | | a=3.14(17)(17) | | x+(x*1.88)=2200 | | a=3.14(17) |

Equations solver categories